Islamic Post-Traditionalism in Indonesia - Rumadi, 1970- (Book collections on Project MUSE., 2015)
Troubled Transit considers the situation of asylum seekers stuck in limbo in Indonesia from a number of perspectives. It presents not only the narratives of many transit migrants but also the perceptions of Indonesian authorities and of representatives of international and non-government organizations responsible for the care of transiting asylum seekers. Fascinated by the extraordinary and seemingly limitless resilience shown by asylum seekers during their often lengthy and dangerous journeys, the author highlights one particular fragment of their journeys - their time in Indonesia, whic.